Water absorbency of super absorbent polymer based on flexible polymeric network. (5th March 2022) - Qi, Zhenming; Hu, Xiaosai
Graphical abstract: Highlights: Water absorbency of the physically cross-linked SAP was investigated. SAP was endowed with a flexible polymeric network under the support of physical nanoparticle cross-linker. As-obtained SAP showed a remarkably increased water-absorbing capacity in distilled water, salt solution and urea solution. Abstract: Flexible polymeric network plays a crucial role for the water-absorbing capability of super absorbent polymers (SAPs). However, most of the chemical cross-linked SAPs show poor water absorbency due to their rigid networks. In the present work, by creating a high elastic framework for SAP under the support of nanoparticles as physical cross-linker, one novel potassium ion-based SAP (K-SAP) with a remarkably increased water uptake was achieved via in-situ copolymerization of acrylic acid and (3-acrylamidopropyl)trimethylammonium chloride. The water-absorbing capacity can reach 3600 g/g in distilled water, 150 g/g in 0.9 wt% KCl solution, 130 g/g in 0.9 wt% NaCl solution and 2250 g/g in 10 wt% urea solution. Furthermore, an improved water-retention performance and recyclability were also achieved due to the firm network structure created by chelation between nanoparticles and polymeric chains. This work opens a new path to endow K-SAP with a super-high water absorbency by constructing a flexible polymeric network for K-SAP under the help of physical cross-linker, which may have promising applications in waste-water treatment, hygienic products, drug delivery system and agriculture.